2019
DOI: 10.3310/hta23470
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural activation therapy for post-stroke depression: the BEADS feasibility RCT

Abstract: Background There is currently insufficient evidence for the clinical effectiveness and cost-effectiveness of psychological therapies for post-stroke depression. Objective To evaluate the feasibility of undertaking a definitive trial to evaluate the clinical effectiveness and cost-effectiveness of behavioural activation (BA) compared with usual stroke care for treating post-stroke depression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 99 publications
4
58
0
1
Order By: Relevance
“…Recruitment of community-dwelling stroke survivors to participate in intervention studies is challenging, particularly among those with poststroke depression [ 53 ]. In this study, recruitment was impacted by COVID-19 closures, though our recruitment rates were similar to a recent intervention study to ameliorate poststroke depression [ 54 ]. Few studies have examined the effect of Tai Chi on poststroke depression [ 36 , 37 , 55 ], though they reported high study retention rates ranging from 85 to 90%, though less than the 100% retention in this study.…”
Section: Discussionsupporting
confidence: 59%
“…Recruitment of community-dwelling stroke survivors to participate in intervention studies is challenging, particularly among those with poststroke depression [ 53 ]. In this study, recruitment was impacted by COVID-19 closures, though our recruitment rates were similar to a recent intervention study to ameliorate poststroke depression [ 54 ]. Few studies have examined the effect of Tai Chi on poststroke depression [ 36 , 37 , 55 ], though they reported high study retention rates ranging from 85 to 90%, though less than the 100% retention in this study.…”
Section: Discussionsupporting
confidence: 59%
“…Meanwhile, in another study on poststroke mind–body problems, acupuncture combined with YYJQE revealed superior improvement effects on the motor function scores and self-rated depression scale scores. To date, previous studies of evidence-based Qigong exercises for treating PSD were extremely limited ( Thomas et al, 2019 ; Hordacre et al, 2021 ). One meta-analysis has been proposed but with a lack of evidence concerning its effects conclusion ( Dong et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the scores of PHQ-9, GAD-7, and PSQI, reduction rate was also used to evaluate the therapeutic effect of the iMBSR. Following standard practice of calculating reduction rate ( 31 ), the formula: reduction rate = (baseline score – score after intervention)/baseline score × 100% was adopted.…”
Section: Methodsmentioning
confidence: 99%